2002
DOI: 10.1007/bf03167448
|View full text |Cite
|
Sign up to set email alerts
|

A functional fitting Runge-Kutta-Nyström method with variable coefficients

Abstract: A new type of variable coefficient Runge-Kutta-Nyström methods is proposed for solving the initial value problems of the special form y"(t) = f (t, y(t)). The method is based on the exact integration of some given functions. If the second derivative of the solution is a linear combination of these functions, then the method is exact, and if this is not the case, the algebraic order (order of accuracy) of the method is very important. The algebraic order of the method is investigated by using the power series e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 14 publications
1
18
0
Order By: Relevance
“…In [8] and [9], Ai = 0 and Fz = A for all i, that is, there exist s unknowns in each of the simultaneous equations, and all the functions Om (t) (m = 1, ..., s) are used to determine these coefficients. Therefore, the resulting method is necessarily a fully implicit one.…”
Section: Functionally Fitted Runge-kutta Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In [8] and [9], Ai = 0 and Fz = A for all i, that is, there exist s unknowns in each of the simultaneous equations, and all the functions Om (t) (m = 1, ..., s) are used to determine these coefficients. Therefore, the resulting method is necessarily a fully implicit one.…”
Section: Functionally Fitted Runge-kutta Methodsmentioning
confidence: 99%
“…[2], [7], [10], [11], [13], [14]). To be able to fit Runge-Kutta (-Nystrom) methods to any desired functions, Ozawa [8], [9] has recently developed a technique to construct the RungeKutta (-Nystrom) method that is exact on the linear space of given functions. When the functions are polynomials, the method reduces to the collocation Runge-Kutta methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16]). Thus, the coefficients b(t, h), d(t, h), A(t, h) converge to those of the conventional EPTRKN method when h → 0.…”
Section: This Impliesmentioning
confidence: 99%
“…For example, trigonometric methods have been developed to solve periodic or nearly periodic problems (see, e.g., [7], [11], [17]). Numerical experiments have shown that trigonometrically-fitted methods are superior to classical Runge-Kutta methods for solving ODEs whose solutions are periodic or nearly periodic functions with known frequencies (see, e.g., [8], [11], [12], [13], [14], [16], [17]). …”
Section: Introductionmentioning
confidence: 99%